2008
DOI: 10.1117/12.797541
|View full text |Cite
|
Sign up to set email alerts
|

Integrated quantum efficiency, reflectance, topography and stress metrology for solar cell manufacturing

Abstract: We report application of phase shifting interferometric measurements to study of the spatially resolved quantum efficiency (QE) of the semiconductor solar-cells. In our method solar-cell is illuminated by two sets of mutually spatially orthogonal fringe patterns of known frequency, and varying phase (shifted phase). We report theoretical results obtained using simple analytical model describing properties of small spot size defects, and preliminary experimental results validating this method. The new method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In addition, we investigated the possibility of combining FPT metrology with photo conductivity mapping metrology [2]. The results showed that the same illumination system used for the topography metrology can be used for probing of the photoelectric properties of the solar cell.…”
Section: •Stress Measurement In Solar Cells and Other Devices •Flatne...mentioning
confidence: 99%
“…In addition, we investigated the possibility of combining FPT metrology with photo conductivity mapping metrology [2]. The results showed that the same illumination system used for the topography metrology can be used for probing of the photoelectric properties of the solar cell.…”
Section: •Stress Measurement In Solar Cells and Other Devices •Flatne...mentioning
confidence: 99%